(untitled) (Theatrum historiae, 2008)
The School sisters de Notre Dame focused on upbringing and education of not only the girl’s youth. They were the most widespread school congregation that worked in the Czech lands of 19 and 20 centuries. Their primary aim was to establish and run girl’s general schools (Trivialschule) and later burgess schools too. These were usually connected with boarding establishment. The author summarizes the results of her probe that should analyse the orphanages that were run by the School sisters de Notre Dame on the territory of the České Budějovice diocese. The first orphanage that was administred by the congregation was the town orphanage in Tábor in 1880. In 1920 they already controlled 44 orphanages in Bohemia. In the České Budějovice diocese they worked in 14 orphanages. There lived children between 6 and 13 (exceptionally 14) years and there were between 10 and 30 children per one establishment. The author analyses everyday life in these orphanages (daily activities, board, financial subvention, etc.) and she deals also with the topic of education of „troubled“ children and the rigorous style of upbringing that was practiced by the School sisters de Notre Dame.